Exploratory analysis of the Hendrick & Hendrick’s Love Attitudes Scale in Psychology students from a private university at Arequipa - Arias Gallegos, Walter (2023)
In this psychometric research he aim was to value the validity and the reliability of the Hendrick and Hendrick Love Attitudes Scale, in a sample of 106 students of the acreer of Psychology from a private university in Arequipa City (Peru). This is a preliminar and exploratory study that follows the classic and factor test theory criteria. The results indicate that the scale has a three factor structure that explain the 38,64% of the total variance. 29 items were deleted and only three love styles were remain: Storge, Mania and Agape, which obtain adequate reliability indexes.